Notes to understand migration policy with international trade theoretical tools - Alfonso Cebreros; Daniel Chiquiar; Mónica Roa; Martín Tobal (Banco de México, 2017)
This paper develops a standard model of international trade and makes three contributions. First, it shows that when the welfare function of the recipient country reflects the utility of natives, freetrade and free-migration generate isomorphic results, that is, they increase overall welfare but redistribute income by reducing the returns of the scarce factor. Although this result is frequently evoked in academic circles, this document shows that the equivalence holds for the most relevant measure of welfare from a political economy perspective. Second, this equivalence is extended to the public policy domain: for each level of trade restrictions mutually imposed, it is found an immigration tax that generates the same redistribution and welfare impacts. Third, in the light of these results, the model is enlarged to illustrate a channel through which political economy concerns may influence immigration policy.
Keywords: F22; F13; D72; D78; 330; International Migration; Political Economy; International Trade